Bacteroides fragilis strain ZY-312 facilitates colonic mucosa regeneration in colitis via motivating STAT3 signaling pathway induced by IL-22 from ILC3 secretion - Zhang, Wendi; Zhou, Qian; Liu, Hongbin; Xu, Jiahui; Huang, Ruo; Shen, Binhai; Guo, Yandong; Ai, Xiuyun; Xu, Jun; Zhao, Xinmei; Liu, Yangyang; Wang, Ye; et al. (Frontiers in Immunology, 2023)
Introduction Probiotics play critical roles in relieving inflammatory bowel disease (IBD). However, the underlying mechanism of Bacteroides fragilis strain ZY-312 (B. fragilis) for colonic mucosa regeneration in IBD remains unclear. Methods The weight loss, disease activity index (DAI), colon length, and histopathology-associated index (HAI) were evaluated the therapeutic effects of B. fragilis in a DSS-induced colitis mouse model. Colonic mucosa proliferation and apoptosis level, and mucus density were detected by histological stain. Gut microbiota was sequenced by 16srRNA analysis. The expression of signal transducer and activator of transcription 3 (STAT3) phosphorylation in colonic mucosa was detected in B. fragilis-treated mice in colitis. B. fragilis-regulated immunity factors of motivating downstream STAT3 phosphorylation were screened by ELISA and flow cytometry. Lastly, B. fragilis-mediated colonic mucosa regeneration effects were verified though the knockout of STAT3 (Stat3△IEC) and IL-22 (IL-22-/-) in mice, and inhibitor of STAT3 and IL-22 in co-culture model. Results B. fragilis alleviated DSS-induced colitis in mice with less weight loss, DAI, colon length shortening, and HAI. Further the results showed that B. fragilis motivated STAT3 phosphorylation in colonic mucosa with the upregulation of proliferation index Ki-67 and mucus density, the downregulation of apoptosis level, and the modulation of gut microbiota through a Stat3△IEC mice model and STAT3 inhibitor-added model in vitro. Meanhwhile we found that B. fragilis promoted IL-22 production, and increased the percentage of IL-22-secreting type 3 innate lymphocytes (ILC3) in colitis. Consequently, We identified that B. fragilis did not increase the expression of pSTAT3, either proliferation level, mucus density, or alter gut microbiota in IL-22-/- mice. Discussion B. fragilis may indirectly motivate ILC3 to secrete IL-22, followed by IL-22-induced STAT3 phosphorylation, hence promoting colonic mucosa regeneration in colitis. It indicates that B. fragilis has the potential to be a biological agent for IBD therapy.